IDENTIFIKASI SEKTOR UNGGULAN DI PROVINSI MALUKU - Darwis Amin (IAIN Ambon, 2017)
This research aims to analyze and determine: (1) economic structure in Province of Maluku and 2) key sectors becoming a development priority. This research uses input-output analysis, which is based on the table data of input-output domestic transactions of Maluku in 2007 based on the producer price which is the last year data published by the classification of 9 economic sectors. The research data is secondary data with data collection technique through documentation and reports research relevant to the research discussion. The results showed that (1) the largest IDK value (above average) was obtained in the trade, hotels and restaurants, agriculture, manufacturing as well as transportation and communication sectors. Then to assess the largest IDP value (above average) is obtained at building sector and manufacturing industry sector. 2) The manufacturing industry sector is the only featured sector in Province of Maluku, while sectors that have strong bearing capacity is agricultural, trade, hotels and restaurants as well as transportation and communications sectors. The sector groups which has high dependency; among others, construction sector. The sector which lacks of prospects are mining and digging, electricity, gas and fresh water, finance, leasing and company services as well as the service sectors. Key words: featured sector, IDK and IDP value, Province of Maluku